Soluble Interleukin-2 Receptor Level as a Marker of Hemophagocytic Lymphohistiocytosis in Children With Severe Dengue - Singh, Dhirendra; Raghunathan, Veena; Dhaliwal, Maninder; Rastogi, Neha; Chadha, Ritu; Yadav, Satya Prakash (Frontiers in Pediatrics, 2021)
Dengue induced hemophagocytic lymphohistiocytosis (HLH) is increasingly recognized as an important cause of secondary HLH. Early identification of dengue HLH and directed therapy for HLH may help to alter the outcomes in critically ill patients. Soluble interleukin 2 receptor (IL2R) is a useful inflammatory marker and seen to correlate with HLH disease activity. There is scarcity of data on IL2R in pediatric dengue patients with HLH. All patients (age < 18 years) with severe dengue confirmed by positive Dengue IgM ELISA admitted to PICU were retrospectively enrolled. Patients were screened for presence of HLH. Hemogram, ferritin, fibrinogen, liver, and renal function test, IL2R levels were noted. Out of 15 patients, nine patients met the criteria of HLH. IL2R levels were high in all HLH patients. (mean 51711, range 18000-98715 pg/ml). Mean ferritin levels was high in the HLH group as compared to non HLH group (mean ferritin 34593 vs 3206 ng/ml; p-value 0.004). Liver dysfunction was notably higher in the HLH group compared to non HLH group (mean alanine aminotransferase 6621 U/L vs 165.6 U/L; p- value 0.04, mean aspartate aminotransferase 2145 U/L vs 104.2 U/L; 0.04, bilirubin level 4.2 mg/dl vs 0.7 mg/dl; p- value 0.03). Four patients in the HLH group had acute kidney injury (AKI) and 2 required renal replacement therapy in the form of sustained low efficiency dialysis (SLED). Requirement for invasive ventilation was exclusively seen in HLH group and 3 patients developed ARDS. Two patients each in HLH and non HLH group had shock requiring vasoactive therapy in addition to fluids. Mean days of ICUand Hospital stay were higher in HLH group vs Non HLH group but not statistically significant (6.4 vs 4.4: p-value 0.32 and 8.44 vs 5.6; P-value 0.18 days respectively). All children in HLH group received steroids as per HLH protocol. In the HLH group,7 survived while 2 died. In the non HLH group, all 5 patients survived. We concluded that, IL2R levels are high in dengue HLH and useful for definitive diagnosis. Early recognition of this condition in severe dengue and prompt appropriate treatment with steroids improves chances of better outcome.